An Intrarenal Adrenocortical Carcinoma Arising in an Adrenal Rest - Ji Hee Lee; Young Deuk Choi; Nam Hoon Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
We describe a case of a 61-year-old Korean man who was diagnosed with renal cell carcinoma that was discovered on abdominopelvic computed tomography obtained after the patient complained of back pain. A radical nephrectomy was performed, and the surgical specimen showed a relatively well-circumscribed and yellowish lobulated hard mass. Microscopically, the tumor showed sheets and nests of hypercellular pleomorphic cells with thick fibrous septation, frequent mitoses, and areas of adrenal cortical-like tissue. Immunohistochemical staining revealed that the tumor cells were positive for inhibin-α, vimentin, synaptophysin, and melan A. It also revealed that the tumor cells were negative for pan-cytokeratin, epithelial membrane antigen, paired box 8, α-methylacyl-coenzyme A racemase, CD10, cytokeratin 7, carbonic anhydrase 9, c-Kit, renal cell carcinoma, transcription factor E3, human melanoma black 45, desmin, smooth muscle actin, S-100, chromogranin A, CD34, anaplastic lymphoma kinase, and integrase interactor 1. Based on these histopathological and immunohistochemical findings, we diagnosed the tumor as intrarenal adrenocortical carcinoma arising in an adrenal rest. Several cases of intrarenal adrenocortical carcinoma have been reported, although they are very rare. Due to its poor prognosis and common recurrence or metastasis, clinicians and pathologists must be aware of this entity.